Linguistic Hybridity: The Use of Code Mixing in Nepali Folk Pop Songs - Saud, Mohan Singh (Journal of NELTA Gandaki, 2022)
Code mixing of two or more languages has become a common phenomenon in Nepali folk pop songs. In this context, this study discussed the phenomenon of mixing multilingual terms in Nepali folk pop songs and the reasons for mixing such codes from other languages. This qualitative phenomenological study along with situation analysis used documents and unstructured interviews as the data collection tools. I selected 12 Nepali folk pop songs purposively for analysis. They include Baduliko Khutko (“Sound of a Hiccup”), Champa (“Champa girl”), “Hello Hello”, Meri Chhoretti (“My Girl Friend”), Mudda Haldincchu (“File a Case”) and Rato Rato Khursani Piro Chha (“Red, Red Pepper Hot”), Chorut Salkauane (“Light a Cigarette”),“Cocacola Figure” and DJ Bajako (“Playing DJ”), Daru Sadkaune (“Gulping Local Wine”) and Hi Kali (“Hello Beauty”), and Tension Naleu Yaar (“Don’t be in Tension, Friend”). These songs were played in the audio laboratory to identify the multilingual terms used by the Nepali composers and musicians in Nepali folk pop songs and analyzed in terms of the phenomenon of code mixing. Two language teachers and one folk pop singer were interviewed to explore the reasons for code mixing. The result shows that the young generation is mostly attracted towards the folk pop songs with code mixing, and such songs become popular among the youths due to their multilingual flavour. Nepali folk songs have been influenced by the postmodernist tradition, fashion and technological influence. The trend of code mixing in Nepali folk pop songs may lose the linguistic purity thereby resulting linguistic hybridity.